Evaluation of Palliative Care Awareness Among Hospitalized Patients and Their Relatives in Türkiye - Uzgör, Füsun; Özkaraman, Ayşe; Özen, Hülya (Makara Journal of Health Research, 2025)
Background: Today, with the advances in medical knowledge and technology, chronic diseases have increased worldwide in parallel with the prolonging life expectancy and the aging of the population. This has increased the need for palliative care in the delivery of medical services. This study aimed to evaluate the palliative care awareness and level of knowledge of inpatients receiving health services in a university hospital and their relatives in Türkiye. Methods: This cross-sectional study was carried out with 360 patients and their relatives who volunteered to participate in the research. The study data were collected in face-to-face interviews using an individual introduction form and palliative care information and opinion form. Results: Most individuals (84.4%, N = 304) participating in the study had never heard of palliative care before. In participants who had a relative with a chronic disease now/in the past, the rate of those who knew and could explain palliative care was significantly higher than those who had never heard of palliative care (p = 0.013). Conclusions: Palliative care awareness care is low among the population, most of which consists of individuals with chronic diseases and their relatives, who are hospitalized to receive health care.